Social Media as A Tool for Direct Selling Business in Dipolog City, Zamboanga Del Norte - Soledad, Emerald A. (International Journal of Multidisciplinary: Applied Business and Education Research, 2023)
The presence of social media has disrupted the way people live, behave and interact. Philippines is ranked number one as active social media users with an average of 4.17 hours per day. Direct selling businesses in the country continue grow each year, and have introduced new products and expanded new customer reach. With this information presented, the right use of social media will help direct selling businesses reach a well-engaged community of buyers. The research aims to develop relevant marketing strategies to promote the use of social media in direct selling. Descriptive research was being utilized with two sets of researcher-made questionnaires. A pre-survey activity was performed prior to the actual data gathering to validate the reliability of the survey tool. There were one hundred twenty (120) total respondents: comprised of one-hundred (100) direct selling customers and twenty (20) direct sellers, who participated in the data gathering process. Furthermore, the study will use frequencies, percentages, and weighted means for the data treatment. The findings of the study show that Facebook, Twitter, Instagram, and YouTube are the most widely used channels among the respondents of the study. The extent of social media usage by the direct sellers is moderate and social networking site is the most preferred platform to use in doing direct selling-related activities to achieve convenience, productivity, product availability and market growth. Therefore, it can be concluded that social media can be a strategic tool for direct selling business in Dipolog City, Zamboanga del Norte, Philippines.